Natural Hybrid Origin of the Controversial “Species” Clematis × pinnata (Ranunculaceae) Based on Multidisciplinary Evidence - Lyu, Rudan; He, Jian; Luo, Yike; Lin, Lele; Yao, Min; Cheng, Jin; Xie, Lei; Pei, Linying; Yan, Shuangxi; Li, Liangqian (Frontiers in Plant Science, 2021)
Interspecific hybridization is common and has often been viewed as a driving force of plant diversity. However, it raises taxonomic problems and thus impacts biodiversity estimation and biological conservation. Although previous molecular phylogenetic studies suggested that interspecific hybridization may be rather common in Clematis, and artificial hybridization has been widely applied to produce new Clematis cultivars for nearly two centuries, the issue of natural hybridization of Clematis has never been addressed in detail. In this study, we tested the hybrid origin of a mesophytic and cold-adapted vine species, Clematis pinnata, which is a rare and taxonomically controversial taxon endemic to northern China. Using field investigations, flow cytometry (FCM), phylogenomic analysis, morphological statistics, and niche modelling, we tested hybrid origin and species status of C. pinnata. The FCM results showed that all the tested species were homoploid (2n = 16). Phylonet and HyDe analyses based on transcriptome data showed the hybrid origins of C. × pinnata from either C. brevicaudata × C. heracleifolia or C. brevicaudata × C. tubulosa. The plastome phylogeny depicted that C. × pinnata in different sampling sites originated by different hybridization events. Morphological analysis showed intermediacy of C. × pinnata between its putative parental species in many qualitative and quantitative characters. Niche modelling results suggested that C. × pinnata had not been adapted to a novel ecological niche independent of its putative parents. These findings demonstrated that plants of C. × pinnata did not formed a self-evolved clade and should not be treated as a species. The present study also suggests that interspecific hybridization is a common mechanism in Clematis to generate diversity and variation, and it may play an important role in the evolution and diversification of this genus. Our study implies that morphological diversity caused by natural hybridization may overstate the real species diversity in Clematis.